THE EFFECT OF EXTENSION OF LABOR PREPARATION AGAINST THE PRIMIGRAVID MOTHER'S ANXIETY LEVEL WHILE APPROACHING THE LABOR PROCESS IN SINDANG GOODS HEALTH CENTER: PENGARUH PENYULUHAN TENTANG PERSIAPAN PERSALINAN TERHADAP TINGKAT KECEMASAN IBU PRIMIGRAVIDA SAAT MENJELANG PROSES PERSALINAN DI PUSKESMAS SINDANG BARANG - Elpinaria Elpinaria Girsang (Jurnal Ilmiah Wijaya, 2018)
Legal data that belong to Health Department of Indonesia shows that the number of maternal mortality is decreasing. Even though the number of maternal mortality in Indonesia still high, it has already decreased from 307/100.000 births to 216/100.000 births based on Survey of Demographic and Health of Indonesia (SDKI) 2010/2011. To discover the influence of counseling about the preparation of giving birth to the level of anxiety of primigravida before giving birth in Puskesmas Sindang Barang. Quasi-experimental research with Equivalent Control Group Design. In this research design, it is classified into two groups, they are intervention and control by using quota sampling technique. By 36 people as the samples, data is gained by spreading questionnaire and counseling. Based on the analysis of data, it shows that the average level of anxiety after given health education about dysmenorrheal in the intervention group is 1,50, whereas the average level of anxiety after given health education in the control group is 1,06. This shows that there is the difference of the average of dysmenorrheal pain level between group that is given counseling and group that is not given counseling about giving birth preparation. Two independent samples are tested using mann-whitney test to the data that do not distribute abnormally. After mannwhitney test are done, it generates p-value of 0,003. That p-value 0,003 < α (0,05), so Ho is rejected that means there are some influences of counseling of giving birth preparation to the anxiety level of primigravida before giving birth in Puskesmas Sindang Barang. There some influences of counseling about the preparation of giving birth to the anxiety level of primigravida before giving birth in Puskesmas Sindang barang. To improve the implementation of counseling about the preparation of giving birth to the anxiety level of primigravida before giving birth.